PROBLEMATIKA PENDIDIKAN ISLAM DI ERA SOCIETY 5.0 - Wulandari Wulandari (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
This article aims to describe the problems of Islamic education in the era of the society 5.0 related to students, educators, and educational facilities and efforts to overcome them. Problems that become challenges in the implementation of Islamic education include moral degradation of students due to the use of gadgets without intense supervision, teacher limitations in utilizing technology-based learning media, and inadequate infrastructure to support the implementation of Islamic education in schools. Efforts to deal with educational problems with cooperation between parents and teachers to supervise the use of gadgets in students, improve the ability of educators in the use of technology-based learning media through training or seminars, and the provision of adequate Islamic education facilities and infrastructure in accordance with today's technological developments